Supplementatio of beer yeast (Saccharomyes cerevisiae) within the protein food in bees (Apis Mellifera) in the Quinindé canton, parroquia Rosa Zarate - Añazco Chávez, Joffre Paúl; Cantos Cruz, Mayra Verónica; Plaza Cedeño, Eugenio David; Morales Moreira, Johann Santiago (Tierra Infinita, 2022)
Bees are insects that are very important in the natural chain for food production, having the limitation that in winter times or during the establishment of the hive, there is a precarious or null amount of nutrients necessary for their individual and population maintenance, proportionally decreasing the general production of the apiary, being necessary to determine the acceptability of artificial protein supplements in newly established hives as an aid to their adaptability and weight gain of the apiary. In this research, an analysis of the acceptability and influence of protein supplementation of artificial origin on the number, weight and production of the members of the hive is carried out. The experiment was carried out in the dry season, six hives were used with a capture time between 1 - 15 days before the start of the investigation. The trial-error technique was used in order to determine the acceptability of an artificial protein supplement that allows improving the vigor of the hive and whose data obtained were quantified to determine the results. The protein cake was composed of lentil flour, corn flour and brewer’s yeast with 20% protein. The results showed acceptability of the artificial protein supplement that allowed to achieve a higher average weight of the production and numerical increase of the members of the hive, so the use of these supplements becomes essential in times of food scarcity.